2019
DOI: 10.1101/647578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrin-alpha-6+ Stem Cells (ISCs) are responsible for whole body regeneration in an invertebrate chordate

Abstract: Colonial ascidians such as Botrylloides are the only chordates able to undergo whole body regeneration (WBR), during which entire new bodies can be regenerated from small fragments of blood vessels. Although it has long been suspected that undifferentiated blood borne cells called hemoblasts play an important role, the cellular and molecular mechanisms of this regeneration process are poorly understood. Here, we show that during the early stages of WBR, proliferation occurs only in small, blood borne cells tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Despite efforts in the last decade to characterize the cells building vascular buds (Brown, Keeling, Le, & Swalla, 2009;Rinkevich et al, 2010;Sunanaga, Inubushi, & Kawamura, 2010;Sunanaga, Saito, & Kawamura, 2006;Voskoboynik et al, 2007), their nature has remained elusive. Only very recently, Kassmer et al (2019) showed that injection of a single Integrin-alpha6-positive (IA6+) hemoblast in a colony of Botrylloides leachii previously treated with a mitosis inhibitor can rescue budding capacities. The number of IA6+hemoblasts rapidly increases at the onset of vascular budding, participating in the formation of the bud tissues (Kassmer et al, 2019).…”
Section: Budding In Stolidobranchia: the Peribranchial The Vascular… And The Vasalmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite efforts in the last decade to characterize the cells building vascular buds (Brown, Keeling, Le, & Swalla, 2009;Rinkevich et al, 2010;Sunanaga, Inubushi, & Kawamura, 2010;Sunanaga, Saito, & Kawamura, 2006;Voskoboynik et al, 2007), their nature has remained elusive. Only very recently, Kassmer et al (2019) showed that injection of a single Integrin-alpha6-positive (IA6+) hemoblast in a colony of Botrylloides leachii previously treated with a mitosis inhibitor can rescue budding capacities. The number of IA6+hemoblasts rapidly increases at the onset of vascular budding, participating in the formation of the bud tissues (Kassmer et al, 2019).…”
Section: Budding In Stolidobranchia: the Peribranchial The Vascular… And The Vasalmentioning
confidence: 99%
“…Only very recently, Kassmer et al (2019) showed that injection of a single Integrin-alpha6-positive (IA6+) hemoblast in a colony of Botrylloides leachii previously treated with a mitosis inhibitor can rescue budding capacities. The number of IA6+hemoblasts rapidly increases at the onset of vascular budding, participating in the formation of the bud tissues (Kassmer et al, 2019). Taken together, these results functionally show for the first time the presence of blood-borne multipotent stem cells in Botrylloides leachii.…”
Section: Budding In Stolidobranchia: the Peribranchial The Vascular… And The Vasalmentioning
confidence: 99%
See 2 more Smart Citations
“…In the other two ascidian species, Botrylloides leachii and Perophora viridis, a population of adult pluripotent stem cells circulating in the hemolymph seems to be responsible of the regeneration of the whole body, including the entire musculature [ 176 , 177 ]. As for solitary species, the study of these cell populations is still in its infancy.…”
Section: Tunicates: the Sister Group Of Vertebratesmentioning
confidence: 99%